Children's role in the community response to HIV in Zimbabwe. Issue 1 (4th February 2013) - Skovdal, Morten; Magutshwa‐Zitha, Sitholubuhle; Campbell, Catherine; Nyamukapa, Constance; Gregson, Simon
Abstract : Introduction: Recent debates on how to achieve an optimal HIV response are dominated by intervention strategies that fail to recognize children's role in the community response to HIV. Whilst formal responses are key to the HIV response, they must recognize and build on indigenous community resources. This study examines adult's perspectives on the role of children in the HIV response in the Matobo District of southern Zimbabwe. Methods: Through a mix of individual interviews ( n =19) and focus group discussions ( n =9), 90 community members who were active in social groups spoke about their community response to HIV. Transcripts were subjected to a thematic analysis and coding to generate key concepts and representations. Findings: In the wake of the HIV epidemic, traditional views of children's social value as domestic "helpers" have evolved into them being regarded as capable and competent actors in the care and support of people living with HIV or AIDS, and as integral to household survival. Yet concurrent representations of children with excessive caregiving responsibilities as potentially vulnerable and at risk suggest that there is a limit to the role of children in the HIV response. Conclusion: Community volunteers and health staff delivering HIV services need to recognize the "behind the scene" role of children in the HIV response and ensure that children are incorporated into their modus operandi – both as social actors and as individuals in need of support.